2013
DOI: 10.1371/journal.pone.0060973
|View full text |Cite
|
Sign up to set email alerts
|

A Quadruple Knockout of lasIR and rhlIR of Pseudomonas aeruginosa PAO1 That Retains Wild-Type Twitching Motility Has Equivalent Infectivity and Persistence to PAO1 in a Mouse Model of Lung Infection

Abstract: It has been widely reported that quorum-sensing incapable strains of Pseudomonas aeruginosa are less virulent than wild type strains. However, quorum sensing mutants of P. aeruginosa have been shown to develop other spontaneous mutations under prolonged culture conditions, and one of the phenotypes of P. aeruginosa that is frequently affected by this phenomenon is type IV pili-dependent motility, referred to as twitching motility. As twitching motility has been reported to be important for adhesion and colonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
(44 reference statements)
3
11
1
Order By: Relevance
“…Apparently, that phenotype is high virulence. Consistent with our results and interpretation, the quadruple ΔlasI, ΔlasR, ΔrhlI, ΔrhlR mutant remains virulent in a mouse lung infection model (29). Lastly, we note that the double lasR, rhlR null mutant is not hypervirulent in the nematode assay.…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, that phenotype is high virulence. Consistent with our results and interpretation, the quadruple ΔlasI, ΔlasR, ΔrhlI, ΔrhlR mutant remains virulent in a mouse lung infection model (29). Lastly, we note that the double lasR, rhlR null mutant is not hypervirulent in the nematode assay.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a quadruple mutant that affects quorum sensing by deletion of genes responsible for synthesizing the signaling molecules or their receptors ( lasIRrhlIR ) did not show a phenotype in the acute lung infection model. This is consistent with the idea that quorum sensing is only required in the chronic phase of the infection and confirms the idea that the phenotype of the bfmS deletion is not due to the impact on quorum sensing.…”
Section: Vertebrate Animal Modelssupporting
confidence: 90%
“…We believe that the relationship between Anr and HHQ in quorum sensing mutants may functionally compensate for effects of losing LasR, and this could help explain the ability for P. aeruginosa lasR mutants to thrive in infections. A recent study demonstrated equal infectivity between WT PAO1 and a lasRI rhlRI quadruple mutant in a mouse lung model, suggesting that homoserine lactone signaling in general may be dispensable for infection in this context (85). Future studies will be aimed at measuring the role for Anr regulation of HHQ production in infections.…”
Section: Discussionmentioning
confidence: 96%